A Study on Translation of Network Catchwords Guided by Skopos Theory - Zheng, Hui (Pacific International Journal, 2025)
With the development of the Internet, Network catchwords have become an important carrier for cross-cultural communication. However, their English translations often suffer from inaccuracy and do not conform to English expression habits. Guided by the Skopos Theory and adhering to the principles of "fidelity" and "eliminating cultural differences", this study proposes four specific translation methods for Network Catchwords: literal translation, literal translation with annotations, free translation, and transliteration. These methods are based on the three major characteristics:，that is，creativity, simplicity, and temporal spirit. The study validates these methods through recent popular cases such as "power of silver hair", "lying flat", "carry the can", and "Moutai". The research results show that choosing appropriate translation methods based on the characteristics of Network catchwords can effectively solve the translation pain points, accurately convey the meaning, and adapt to the cultural connotations. This study not only provides a practical path and abundant cases for the English translation of Network catchwords, filling the gap in theoretical research and standardized practice in this field, but also helps Chinese social culture reach the world through precise language conversion, enhancing the international dissemination and influence of Chinese culture.